2018
DOI: 10.1186/s40985-018-0100-0
|View full text |Cite
|
Sign up to set email alerts
|

Participation in lung cancer screening programs: are there gender and social differences? A systematic review

Abstract: Lung cancer remains the leading cause of cancer mortality worldwide. A number of screening trials for early detection of lung cancer exist, using chest X-ray, low-dose computed tomography, or both. However, little is known about the socio-demographic characteristics of participants in lung cancer screening programs. As gender and socio-economic determinants are important variables to consider for successful program implementation, this review aims to characterize the participants in such programs and to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 37 publications
1
51
0
Order By: Relevance
“…In a recently published systematic review, researchers found over-representation of male participants in LCS programs. 25…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published systematic review, researchers found over-representation of male participants in LCS programs. 25…”
Section: Discussionmentioning
confidence: 99%
“…Based on our prior studies in the LCS setting, we project a 45% participation rate, 95% completion of the CT screening exam, and a 5%−20% loss at each follow-up assessment [16]. Also, based on the current trends in the demographic characteristics of individuals undergoing LCS [23], as well as what is typically found in new cancer screening modalities, we expect that the majority of participants will be insured, white, and non-Hispanic. This will be a limitation of all studies conducted within LCS settings until screening becomes more widely integrated and promoted in clinical settings.…”
Section: Methodsmentioning
confidence: 99%
“…Reported attitudes to lung cancer screening are complex and are influenced by multiple factors including practical and emotional barriers, avoidant and fatalistic beliefs, fear, stigmatization, willingness to undergo surgery, low perceived risk of lung cancer and/or benefits of screening, knowledge barriers and dislike of healthcare services . 37,38,[48][49][50][51][52][53] In healthcare systems where screening is not fully funded, costs paid by the screenee also play a role in screening uptake. [52][53][54] Relatively few studies have sought to understand individuals' motivation for participating in lung cancer screening.…”
Section: Attitudes and Motivationmentioning
confidence: 99%
“…Attitudes towards lung cancer screening vary and will influence screening uptake. Reported attitudes to lung cancer screening are complex and are influenced by multiple factors including practical and emotional barriers, avoidant and fatalistic beliefs, fear, stigmatization, willingness to undergo surgery, low perceived risk of lung cancer and/or benefits of screening, knowledge barriers and dislike of healthcare services 37,38,48–53 . In healthcare systems where screening is not fully funded, costs paid by the screenee also play a role in screening uptake 52–54 …”
Section: Attitudes and Motivationmentioning
confidence: 99%